Influence of welding current variation on the geometric characteristics of the weld bead in CA50 rebar steel using shielded metal arc welding and MIG/MAG Processes with overlay joint (Research, Society and Development, 2024)
The construction industry is an important parameter of economic development, driving the search for techniques and products with improved performance. Weldable rebar steels are widely used in the construction sector, especially in reinforced concrete, due to their diverse mechanical properties. CA50 steel is widely known for its weldability, which instills confidence in the structure. Therefore, this study aims to investigate the heat input and geometric characteristics of welded joints using shielded metal arc welding and MIG/MAG processes with overlay joint, employing three different welding current variations. Approximately 100mm samples of CA50 rebar steel were prepared and welded using AWS E11018-M covered electrode and MIG/MAG. The weld bead had a length of 100mm with equal spacing according to ABNT NBR 6118:2003 standard. Welding time was measured to calculate heat input, and the samples were cut horizontally using a band saw. Metallographic procedures for revealing the macrography of the fusion zone (FZ) and heat-affected zone (HAZ) utilized optical microscopy techniques. It is concluded that overlay welding of CA50 rebar steel with shielded metal arc welding did not exhibit good geometric aspects such as penetration and weld width at low welding currents, while the MIG/MAG process indicated good welding characteristics at the current parameters, thus enabling rebar welding with overlay joint in the construction sector using the parameters employed.